Blended English: Technology-enhanced teaching and learning in English literary studies. (July 2018) - Milthorpe, Naomi; Clarke, Robert; Fletcher, Lisa; Moore, Robbie; Stark, Hannah
This article provides an account of a collaborative teaching and learning project conducted in the English programme at the University of Tasmania in 2015. The project, Blended English, involved the development, implementation, and evaluation of learning and teaching activities using online and mobile technologies for undergraduate English units. The authors draw on the project's findings from survey and focus group data, and staff reflective practice and peer review, to make the case for increasing technology-enhanced teaching and learning in English literary studies. The blended approach described in this article has the capacity to enhance disciplinary learning; increase accessibility for students in remote and regional areas; facilitate deeper scholarly enquiry; and encourage staff to develop innovative, collaborative, and flexible teaching and learning practices. Appendix 1 presents examples of the project's practical outcomes, as well as outlines of and reflections on three of the activities developed during the project.